The Miracles of Jesus Viewed from Above - Blackburn, Barry L. (Stone-Campbell journal, 2012)
The traditions in the canonical gospels pertaining to the miracles performed by Jesus frequently attract the attention of historians, exegetes, and apologists, but have often been neglected by systematic theologians. This study intends to demonstrate the fruitfulness of bringing these miracle traditions to bear on reflection concerning the doctrine of the Holy Trinity. Each divine person so participates in Jesus' miracles in such a way as to support and illustrate trinitarian theology.